Analysis of the Politicization of Media Coverage of the MeToo Movement in China and its Impact on Public Opinion - Li, Leyi (International Journal of Social Sciences and Public Administration, 2024)
In recent years, the Metoo movement has aroused widespread social concern, it has transcended being just a social movement and has integrated into a broader political and social context. The study endeavors to investigate how the MeToo movement, originally a social movement focused on sexual harassment and sexual assault, has evolved into a phenomenon with a pronounced politicization tendency. To gain a deeper understanding of the politicization of the MeToo movement and its impact, by analyzing the media coverage of the MeToo movement in China, this study aims to reveal the key drivers of politicization of the movement and explore the impact of this politicization for the movement itself and society.